Cloud Computing Awareness among Practitioners in Yemeni Universities: An Exploratory Study - Almekhlafi, Nabil; Al-Hashedi, Abdullah; Mohsen, Abdulqader M.; Ben Othman, Mohamed Tahar (University of Science and Technology, Yemen, 2018)
Cloud computing is a new IT model adopted by many higher education institutions to gain competitive advantage. This study aims to explore the awareness of cloud computing technology among higher education institutions in Yemen. Using academic and administrative staff as the sample, the participants were asked to show their level of awareness of this emerging technology, the extent they utilize the technology, and to give their opinions about the advantages, challenges, and barriers of using this technology. The findings show high level awareness of cloud computing importance for higher education institutions. Besides, the universities are ready to adopt this technology when they can overcome the most challenges which are cost, Internet speed, privacy, and lack of knowledge on how to apply this technology.